Acute Intermittent Porphyria as a Rare Challenging Neuro-Metabolic Disease; a Case Report - Abed, Elsayed; Saeed, Omer; Abd El-Hamid, Basem; Elsayed, Mohamed; Dawoud, Heba; Heikal, Nahla; Elshafie, Ahmed; Hagar, Aya; Emam, Hossam; El-adawey, Ahmed Farag; Fayed, Abdel-Ghaffar; Elsheshiny, Ahmed Hassan; et al. (Archives of Academic Emergency Medicine, 2022)
Porphyria is a challenging metabolic disease due to its heterogeneous presentation symptoms and its difficult diagnosis. Many affected individuals can complain of recurrent neuro-visceral attacks per year, some of which may be persistent and life-threatening, which is confusing if there is no established diagnosis. Although the motor manifestations, autonomic changes and seizure are highly suggestive, the diagnosis is often overlooked and needs confirmatory genetic testing. To the best of our knowledge, the acute intermittent porphyria (AIP) reported in this case, involving severe electrolyte disturbances and rapid severe weakness is a challenging neuro-metabolic case and is extremely rare worldwide. Here, we reported a case of AIP in a young girl who presented to the emergency department of Al-Araby international Hospital, Monufia, Egypt with severe abdominal pain, constipation, and headache which had started 10 days ago. It seems that the diagnosis of porphyria should be considered particularly in those patients with abdominal complaints associated with electrolyte disturbances, seizures, and severe progressive neuropathy.